The Relation Between Burnout ,Optimism and Support From Management of some Faculties in A sample of Teachers at Tishreen University - Sbeira, Fouad; Halloum, Soher (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The aim of this study was to investigate the relation between Burnout, Optimism and Support from Management in some Applied and Theoretical Faculties in a sample of teachers at Tishreen University. The sample consists of120 teachers, who were recruited from some Applied Faculties (Economy, Sciences, Civil Engineering, Electrical and mechanical engineering, and Pharmacy) and from some Theoretical Faculties (Education, Jura and Literatures). We used an adapted and confirmative version of Maslach and others to asses burnout (MBI; Maslach, Jackson, & Leiter,1996) as well as an adapted and confirmative version subscale of the Spector Job Satisfaction Survey to assess support (JSS; Spector, 1995) .Optimism was measured by using an adapted and confirmative version of Satow and Schwarzer Optimism scale (Satow&Schwarzer,(1999. Results indicated that : • There wasno a significant relation between teacher’ s burnout and support they received from the management but there was a significantly positive relation between optimism and support as well as a negative a significantly relation between burnout and optimism • Burnout was negatively associated with experience • No a significantly differences between the mean scores of the teachers in Applied and Theoretical faculties in burnout , optimism and support